Additional records of Elasmopus vachoni Mateus & Mateus, 1966 (Crustacea: Amphipoda: Maeridae) from European waters (Tarifa, southern Spain) - Gouillieux, Benoit; Guerra-García, Jose Manuel; Sorbe, Jean Claude (Zootaxa, 2017)
Additional records of Elasmopus vachoni Mateus and Mateus, 1966 together with description of its its poorly-known mouthparts is provided, based on material from Tarifa Island (southern Spain). The known geographical distribution of this species extends from the Gulf of Guinea to the northern part of the Iberian Peninsula, all along its Atlantic and Mediterranean coast, also extending to Canary and Azores Archipelagos. Additionally, an identification key of Elasmopus species mentioned in European waters (ERMS area) is also given.